Analisis Perubahan Dinamika Abrasi dan Akresi Garis Pantai di Kota Kupang Berbasis Teknologi Penginderaan Jauh - N. Nawa, Nessa; Jong Tallo, Amandus; L. Antjak , Antonius; Fallo, Yunus (Jurnal Ekologi, Masyarakat dan Sains, 2025)
Shorelines are dynamic and perpetually evolving due to hydro-oceanographic variables and anthropogenic activity, which influence the processes of erosion and deposition. This study seeks to quantify shoreline alterations and examine the extent of erosion and deposition in coastal Kupang City by employing remote sensing technologies on Landsat image datasets from 2014, 2018, and 2023, obtained from USGS, in conjunction with Geographic Information System (GIS). Analytical methods were implemented via the Digital Shoreline Analysis System (DSAS) within GIS. The results indicated that alterations manifested as abrasion and accretion with differing magnitudes. From 2014 to 2018 and from 2018 to 2023, notable alterations transpired, with the maximum erosion value attaining -37.98 m in the Kelapa Lima sub-district and the peak deposition measuring 187.09 m in the Kota Lama sub-district. From 2014 to 2018, the regions impacted by abrasion in Kelapa Lima, Kota Lama, and Alak measured 4.01 hectares, 0.63 hectares, and 1.24 hectares, respectively. This technology enables the management and analysis of visual data, offering great temporal resolution, cost-effectiveness, and extensive coverage.